2017
DOI: 10.1371/journal.pmed.1002418
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two cash transfer strategies to prevent catastrophic costs for poor tuberculosis-affected households in low- and middle-income countries: An economic modelling study

Abstract: BackgroundIllness-related costs for patients with tuberculosis (TB) ≥20% of pre-illness annual household income predict adverse treatment outcomes and have been termed “catastrophic.” Social protection initiatives, including cash transfers, are endorsed to help prevent catastrophic costs. With this aim, cash transfers may either be provided to defray TB-related costs of households with a confirmed TB diagnosis (termed a “TB-specific” approach); or to increase income of households with high TB risk to strengthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 41 publications
1
38
0
1
Order By: Relevance
“…Under social protection, Rudgard et al [42] suggested that a TB-specific approach (cash transfers for households with a confirmed case of TB) is more effective and affordable than a TB-sensitive (cash transfers for households with a high TB risk to strengthen their economic resilience) approach to reduce TB-specific catastrophic costs. The Government of India has announced the implementation of direct benefit transfer of ≈US$8 per month up to treatment completion for all patients notified with TB (TB-specific approach) [3,38,42,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under social protection, Rudgard et al [42] suggested that a TB-specific approach (cash transfers for households with a confirmed case of TB) is more effective and affordable than a TB-sensitive (cash transfers for households with a high TB risk to strengthen their economic resilience) approach to reduce TB-specific catastrophic costs. The Government of India has announced the implementation of direct benefit transfer of ≈US$8 per month up to treatment completion for all patients notified with TB (TB-specific approach) [3,38,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The Government of India has announced the implementation of direct benefit transfer of ≈US$8 per month up to treatment completion for all patients notified with TB (TB-specific approach) [3,38,42,43]. Further research is recommended to assess the benefits of TB-specific cash transfers on catastrophic costs due to TB, including inequity in India.…”
Section: Discussionmentioning
confidence: 99%
“…Various social protection initiatives such as cash transfers, food baskets and social insurance are endorsed to help prevent catastrophic costs. Cash transfer initiatives can follow one of the three approaches: TB sensitive (broadly to include patients with risk factors or susceptibility to TB), TB specific (exclusively for patients with TB) or TB inclusive approach (including TB as one of the conditions among others) 10…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, both universal health coverage (which addresses direct medical costs) and social protection measures (which addresses direct nonmedical and indirect costs) will be required [12]. An economic modelling study indicates that a TBspecific approach focussing on TB patients might be more cost-effective than a TB-sensitive approach focussing on all people at high risk of developing TB [13].…”
mentioning
confidence: 99%